A hard act to swallow: modern management of eosinophilic oesophagitis. Issue 2 (12th November 2012) - Louis-Auguste, John Richard; Hoare, Jonathan
Abstract : Eosinophilic oesophagitis (EO) is now established as an important cause of oesophageal symptoms. It is presumed to result from eosinophilic activation to dietary antigens, which is limited to the oesophagus. Inflammatory strictures and secondary dysmotility are common and contribute to symptomatology. Current management involves food exclusion diets and swallowed topical steroid. Strictures may require endoscopic dilatation. Relapse is common but strategies for maintaining remission are not well described. Here we describe a patient with severe stricturing EO, whose symptoms were significantly exacerbated by secondary oesophageal spasm. His symptoms were refractory to dietary, endoscopic and medical therapy including parenteral corticosteroid but responded dramatically to diltiazem. Remission was eventually achieved and maintained with azathioprine, and he was able to discontinue the other therapies and relax his dietary restrictions. We discuss the evidence for dietetic, endoscopic and pharmacological interventions for this disease.